2012
DOI: 10.1111/j.1464-410x.2012.11554.x
|View full text |Cite
|
Sign up to set email alerts
|

Elective segmental ureterectomy for transitional cell carcinoma of the ureter: long‐term follow‐up in a series of 73 patients

Abstract: Study Type – Therapy (outcome) Level of Evidence 2b What's known on the subject? and What does the study add? Upper Urinary Tract (UUT) Transitional Cell Carcinoma (TCC) is an uncommon disease and represents approximately 5% of all urothelial carcinomas. We report our series on 73 patients treated with Kidney Sparing Surgery for UUT TCC. Good results have been achieved in terms of oncological outcome comparing this conservative approach to the radical nephrourectomy. OBJECTIVES To report the long‐term oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…12 Simonato et al reported that 5-year CSS rates were 94.1% in 73 patients with distal ureteral tumors treated with DUx. 13 Recently, Dalpiaz et al showed that CSS was 77% for 49 patients treated with DUx, which was comparable with those for patients treated with NUx. 7 However, patient and tumor characteristics of DUx could be intrinsically different from patients with NUx.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…12 Simonato et al reported that 5-year CSS rates were 94.1% in 73 patients with distal ureteral tumors treated with DUx. 13 Recently, Dalpiaz et al showed that CSS was 77% for 49 patients treated with DUx, which was comparable with those for patients treated with NUx. 7 However, patient and tumor characteristics of DUx could be intrinsically different from patients with NUx.…”
Section: Discussionmentioning
confidence: 80%
“…Simonato et al . reported that 5‐year CSS rates were 94.1% in 73 patients with distal ureteral tumors treated with DUx . Recently, Dalpiaz et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding oncological outcomes after conservative treatments we note that there is evidence that distal ureterectomy is as effective and safe as radical nephroureterectomy in terms of cancer specific survival, recurrence free survival and metastasis free survival [34]. Other studies showed no difference in overall survival, cancer specific survival and intravesical recurrence free survival [35][36][37]. Neither is there any significant deterioration in renal function post operatively similar to a multi-institutional study comparing radical and conservative surgeries [38].…”
Section: Discussionmentioning
confidence: 68%
“…Oncologically however, it is evident from studies that segmental or total ureterectomy is not inferior to radical nephroureterectomy. 1 …”
Section: Introductionmentioning
confidence: 99%